2014
DOI: 10.1093/intimm/dxu055
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine is a potent systemic adjuvant for glycoprotein antigens

Abstract: Polyethyleneimine (PEI) is an organic polycation used extensively as a gene and DNA vaccine delivery reagent. Although the DNA targeting activity of PEI is well documented, its immune activating activity is not. We recently reported that PEI has robust mucosal adjuvanticity when administered intranasally with glycoprotein antigens. Here, we show that PEI has strong immune activating activity after systemic delivery. PEI administered subcutaneously with viral glycoprotein (HIV-1 gp140) enhanced antigen-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 28 publications
2
66
0
Order By: Relevance
“…The cationic polymer polyethyleneimine (PEI), long used as a carrier tool for gene transfection, was recently found to be a promising adjuvant [9,10] and was used as a direct therapeutic agent for immunotherapy [11][12][13]. As a potent mucosal adjuvant against viral subunit glycoprotein antigens [9,10], PEI co-administrated with viral vaccine antigen gp140 increased the production of antigen-specific IgG approximately 100 fold, compared to gp140 alone.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The cationic polymer polyethyleneimine (PEI), long used as a carrier tool for gene transfection, was recently found to be a promising adjuvant [9,10] and was used as a direct therapeutic agent for immunotherapy [11][12][13]. As a potent mucosal adjuvant against viral subunit glycoprotein antigens [9,10], PEI co-administrated with viral vaccine antigen gp140 increased the production of antigen-specific IgG approximately 100 fold, compared to gp140 alone.…”
mentioning
confidence: 99%
“…As a potent mucosal adjuvant against viral subunit glycoprotein antigens [9,10], PEI co-administrated with viral vaccine antigen gp140 increased the production of antigen-specific IgG approximately 100 fold, compared to gp140 alone. Size was crucial for the activity of PEI, because PEI of higher molecular weight (750 kDa) and in branched form acted more powerfully than lower molecular weight PEI and its linear form.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, branched PEI is the best research form in terms of gene delivery (25). Recently, it was reported that branched PEI drove a mixed Th1/Th2-type adaptive immune response after systemic delivery (26).…”
Section: Discussionmentioning
confidence: 99%
“…5 Reversely, the small monomers of ethylene glycol pose no effect on immune cells; but when they assemble into nano-to-micro-scale polymers, they further become complex with antigens and potently challenge the antigen-presenting cells. 6,7 As such, it is necessary to take a closer look at the toxicity of modifying agents in their relevant dimension, so as to provide more reliable information on the safer use of processed nanomaterials for biomedical purposes.…”
Section: Introductionmentioning
confidence: 99%